(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the process of applying a pattern composition to plates in Uzbek pottery, its historical roots, artistic and symbolic features. Patterns based on a central-radial composition are considered based on the criteria of structure, symmetry and harmony, and the aesthetic and spiritual content of the pattern elements (floral, geometric, Islamic) is highlighted. Each type of pattern expresses the people’s attitude to nature, religious and philosophical outlook and national values. The article also shows that the practical and aesthetic possibilities of plate patterns are expanding through their integration with modern design and technologies. The results of the research substantiate the need to preserve national art, convey it to the younger generation and interpret it in a global cultural context.